FINANCIAL ANALYSIS OF PT. HUTAMA KARYA (PERSERO) ON THE ASSIGNMENT OF THE TRANS SUMATRA TOLL ROAD PHASE 2 WITH A SERVICE-BASED PERIODIC FINANCING SCHEME (CASE STUDY: BETUNG â TEMPINO â JAMBI TOLL ROAD) - Satyo Anggono, Pulung
Based on Presidential Regulation (Perpres) Number 100 of 2014, it is updated through Presidential Regulation Number 131 of 2022, PT. Hutama Karya (Persero) (referred to as "PTHK") has been assigned by the government to complete the construction of Toll Roads in Sumatra in stages and sustainably, one of which is the Betung - Tempino - Jambi Toll Road, which will be implemented with the Service-Based Periodic Payment (PBBL) scheme. The PBBL scheme is an assignment with a scope that includes planning, funding, construction, operation, and maintenance, and it adopts the Availability Payment (AP) mechanism. Because the PBBL scheme also provides for the scope of funding, PTHK must take out loans to increase financial capacity so that it can be financially closed with limited funding. Therefore, this assignment has the potential to significantly impact PTHK's financial performance so that it can violate the financial covenant agreed upon between PTHK and creditors and corporate bondholders. Therefore, this study aims to determine the impact on the financial covenant of PTHK using the PBBL scheme on the sensitivity of the capital structure and the duration of annual PBBL payments and to provide recommendations to management regarding the use of the PBBL scheme. This study uses quantitative research with primary and secondary data sources that are limited to the scope of financial aspects. The analysis will be implemented by calculating sensitivity to the capital structure, which includes the use of the debt portion to equity and the fair return margin on the equity portion, along with the duration of PBBL payments, which is 10 or 15 years. From the results of the analysis of the impact on the potential for violation of the PTHK financial covenant on the sensitivity of the capital structure and payment duration with the PBBL scheme, it can be concluded that if the Betung - Tempino - Jambi Toll Road uses the PBBL scheme, there is no violation of the PTHK financial covenant if it takes into account the Fair Profit Rate on the equity portion where the requirements of the financial ratio include Debt to Equity Ratio (DER) with the requirement ? 2.5 times, Interest Coverage Ratio (ICR) with the requirement ? 1 time, and Debt Service Coverage Ratio (DSCR) with the requirement ? 1 time. So with the approach of existing rules and regulations, the calculation of the PBBL scheme on the Betung - Tempino - Jambi Toll Road is recommended with a capital structure with a debt of 70% and equity of 30%, an annual payment duration of 15 years, and taking into account the fair return margin on the equity portion.